VKORC1 –1639G>A (rs9923231) Polymorphism and Warfarin Dose Variability in Iraqi Patients with Hematological Disorders: A Pharmacogenetic Case-Control Study: Polimorfisme VKORC1 –1639G>A (rs9923231) dan Variabilitas Dosis Warfarin pada Pasien Irak dengan Gangguan Hematologi: Sebuah Studi Kasus-Kontrol Farmakogenetik - Esraa S. Al-Fatlawey (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Warfarin therapy for thrombotic hematological disorders is complicated by substantial inter-individual dose variability. Specific Background: The VKORC1 –1639G>A polymorphism is a major genetic determinant of warfarin sensitivity, yet Middle Eastern populations remain underrepresented in pharmacogenetic research. Knowledge Gap: There is limited evidence regarding VKORC1 allele distribution and its clinical relevance in Iraqi patients with hematological conditions. Aims: This study aimed to determine VKORC1 genotype frequencies and evaluate their association with warfarin dose, therapeutic control, and predictive modeling. Results: The AA genotype was associated with significantly reduced warfarin dose requirements compared to GG carriers, and VKORC1 explained 31.2% of dose variability. A multi-locus model incorporating additional genetic and clinical variables increased predictive accuracy to 61.3%. Novelty: This study provides the first comprehensive pharmacogenetic characterization of VKORC1 in an Iraqi hematological cohort, integrating cytokine gene variants into dosing models. Implications: These findings support population-specific dosing strategies and highlight the clinical relevance of genotype-guided anticoagulation in Middle Eastern healthcare settings. Keywords: Vkorc1 Polymorphism, Warfarin Dosing, Pharmacogenetics, Hematological Disorders, Iraqi Population Key Findings Highlights Genetic variation strongly differentiates dose requirements among patient groups Combined genetic markers substantially improve predictive modeling accuracy Regional allele distribution reveals distinct population-specific patterns